A paisagem revisitada - Domingues, Álvaro (Finisterra, 2001)
BACK TO LANDSCAPE – Natural landscape in classical geography wasa coherently constructed and universally acknowledged central concept and unquestionably part of geography itself. Hot debate that arose from recent epistemology in geography nearly brought this heritage to an end and even accused it of acting as a brake on the urgent need for scientific renewal. As an old saying goes, what we throw out through the door comes back through every window and not always in the best manner: for some, it is a simple return to the past, although it also poses an external threat to geography’s highest achievement; for others, the impression is that someone has overtaken us in this constant toing and froing that has split the field of geography. However, we maintain that this sudden interest in landscape opens up to us new domains for reflection and investigation, which is, as it was in the past, enriched by the plurality of meanings it embraces. After examining other disciplines (such as aesthetics, anthropology, landscape ecology, and architecture landscape), we return to geographical landscape with the aim of showing a fresh way of looking at things and the new possibilities this concept opens.